High-intensity Functional Training (HIFT) and the Oxford System: Their Effect on the Physical and Skill Factors of Football Players During Weight Training - Hassan Hashim Abdulla; Tareq Hussein Mohammed Salih; Hiwa Ahmed Rahim; Dara Latif Saifaddin (Journal of Coaching and Sports Science, 2025)
Background: Improving the functional fitness of elite football players requires specialized training techniques that align with structured sport-specific programs. High-Intensity Functional Training (HIFT) and the Oxford System are emerging methods incorporated into weightlifting programs to enhance physical and skill-related attributes in football athletes. This study explores their effectiveness compared to traditional weightlifting methods.Aims: The study aims to assess the impact of HIFT and Oxford System exercises on football players' physical and skill development, focusing on explosive force, speed power, maximum speed, dribbling, passing, and scoring.Methods: Twenty-four football players from the Darbandikhan Sports Club (2021–2022 seasons) were purposively allocated into an experimental group (HIFT and Oxford System) and a control group (conventional weightlifting). Physical and skill-related characteristics were measured through pre-tests and post-tests to evaluate improvements.Results: The experimental group significantly improved physical and skill-related attributes between the pre-test and post-test. Post-test results revealed that explosive force, speed power, and maximum speed were significantly higher than in the control group (t = −4.257, p = 0.002). Skill-related dribbling, passing, and scoring improvements were also statistically significant (t = 1.147, p = 0.001; 1.264, p = 0.002; 4.287, p = 0.004). The experimental group outperformed the control group across all measured criteria.Conclusion: The findings indicate that HIFT and Oxford System exercises effectively enhance football players' crucial physical and skill components. Incorporating these training methods into structured programs can significantly improve players' athletic performance.